Numerical study of the spherically symmetric Gross-Pitaevskii equation in two space dimensions - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2000)
The Gross-Pitaevskii equation for Bose-Einstein condensation (BEC) in two space dimensions under the action of a harmonic oscillator trap potential for bosonic atoms with attractive and repulsive interparticle interactions was numerically studied by using time-dependent and time-independent approaches. In both cases, numerical difficulty appeared for large nonlinearity. Nonetheless, the solution of the time-dependent approach exhibited intrinsic oscillation with time iteration which is independent of space and time steps used in discretization.
Keywords: Electrodynamics; Electron transport properties; Electron traps; Electronic density of states; Ground state; Low temperature operations; Nonlinear equations; Oscillations; Bose Einstein condensate; Dilute bosonic atoms; Gross-Pitaevskii equation; Ground state wave function; Repulsive interatomic interactions; Schrodinger equation; Trap energy; Atoms